Immunoglobulin G subclasses of fluorescent anti-Treponema pallidum antibodies: evidence for sequential development of specific anti-T. pallidum immunoglobulin G responses in patients with early syphilis. - van der Sluis, J J (1986)
The development of immunoglobulin G (IgG) subclass-specific anti-Treponema pallidum antibodies during the course of syphilis in humans was studied with sera from 50 untreated male patients. The patients were divided into five diagnosis groups. In the fluorescent treponemal antibody test, which delineates the presence of cross-reacting antibodies, as well as specific antitreponema antibodies, IgG1, IgG2, and IgG3 subclass antibodies were already present during the seronegative primary stage. Specific antibodies, which were detected by the fluorescent treponemal antibody absorption test, were first present during the serotype-variable primary stage. These antibodies were almost exclusively of the IgG1 and IgG3 subclasses. In later stages, antibodies of other subclasses were detectable. Titration of IgG1 antitreponema antibodies in three electrophoretically different IgG fractions revealed an asymmetric distribution in these fractions during primary syphilis. The antibodies were largely confined to the most basic fraction during primary syphilis. A sudden change in the distribution was noted between the end of the primary stage and the secondary stage; an even distribution of IgG1 antitreponema antibodies existed in the late latent stage. These findings confirm and extend previous results from our laboratory. The development of antibodies detected by both tests is discussed in terms of a sequential stimulation of the immune system due to the presence of an extracellular layer covering the treponemas or, alternatively, in terms of a suppression of the immune response during early syphilis.